Processing, thermo-mechanical characterization and gas permeability of thermoplastic starch/poly(butylene trans-1, 4-cyclohexanedicarboxylate) blends. (November 2018) - Genovese, Laura; Dominici, Franco; Gigli, Matteo; Armentano, Ilaria; Lotti, Nadia; Fortunati, Elena; Siracusa, Valentina; Torre, Luigi; Munari, Andrea
Abstract: In this contribution, binary blends of thermoplastic starch (TPS) and poly(butylene trans -1, 4-cyclohexanedicarboxylate) (PBCE) have been prepared by melt extrusion. The effect of different amounts of PBCE and the presence of citric acid as compatibilizer have been studied with respect to the blend behavior. In particular, morphological and thermal studies allowed for the determination of the compatibility between the blend components, and of their characteristic thermal transitions and thermal stability. Envisioning potential packaging applications, surface wettability, moisture absorption and migration of food simulant have been investigated. In addition, mechanical properties and gas permeability have been evaluated after conditioning the films in dry and humid environment. Highlights: Blends of thermoplastic starch and poly(butylene trans -1, 4-cyclohexanedicarboxylate) have been prepared by melt extrusion. The effect of blend composition and of the presence of citric acid have been studied with respect to the blend behavior. Compatibilized binary blends are characterized by improved mechanical and barrier properties to oxygen and carbon dioxide.